Konsep Ilmu Menurut Syed Muhammad Naquib Al-Attas (Analisis buku Islam Dan Filsafat Sains) - Lailah Alfi Alfi (Tasfiyah: Jurnal Pemikiran Islam, 2018)
Concept of Science in Islam is a very important thing to know al-Ḥaqq. Al-Qur'an and Ḥadith contains repeatedly the word “science” and its derivatives, which occupy the second after the word “tawheed”. Al-Attas had said in his work entitled "Islam and Philosophy of Science" that science is based on the Islamic Worldview of tawhīdi, so the concept is clearly different from the concepts that come from the Western secular. According to al-Attas the science includes two things, in order to explain the truth denoted by the term ḥaq which summarizes everything, both propositions and ontologies. The method of obtaining a knowledge is also different from the Western concept, wherein al-Attas explains there are several intermediaries, namely a sound senses, khabar shadiq, sound mind, and intuition.